Multi-echelon reverse logistics network design in the context of circular economy: a Hong Kong case study. - Kang, Kai; Tan, Bing Qing (Humanities & Social Sciences Communications, 2025)
The management of construction and demolition waste (CDW) is emerging as a significant global challenge. Traditional methods such as direct landfill and incineration fail to handle the vast amount of CDW properly, resulting in serious social and environmental issues. In this context, the construction industry has increasingly recognized the importance of CDW recycling and recovery. Consequently, construction industry leaders are advocating for development of reverse logistics networks for multiple types of CDW by solving a multi-objective mixed-integer linear programming model, which aims to restore waste for new structures toward circular economy. This model reduces landfill waste and maximizes the value of CDW, while minimizing total cost and negative environmental impact by integrating with the government under uncertainties to encourage sustainable management of CDW. A real-world case study from Hong Kong is conducted to examine and validate the practicability of the proposed model. Experimental results show that transportation activities have a significant impact on the reverse logistics network design since they are costly and generate the largest share of carbon emissions. In addition, a regulatory mechanism, i.e., setting carbon emission caps, proves effective in balancing facility workload and improving the utilization of underutilized facilities. The results also indicate that the proposed reverse logistics network is capable of adapting to costly transportation scenarios by prioritizing facilities with higher operational costs but lower transportation expenses.